Usage of In Vitro Metabolism Data for Drug‐Drug Interaction in Physiologically Based Pharmacokinetic Analysis Submissions to the US Food and Drug Administration. (9th February 2021) - Lee, Jieon; Yang, Yuching; Zhang, Xinyuan; Fan, Jianghong; Grimstein, Manuela; Zhu, Hao; Wang, Yaning
Abstract: The key parameters necessary to predict drug‐drug interactions (DDIs) are intrinsic clearance (CLint ) and fractional contribution of the metabolizing enzyme toward total metabolism (fm ). Herein, we summarize the accumulated knowledge from 53 approved new drug applications submitted to the Office of Clinical Pharmacology, US Food and Drug Administration, from 2016 to 2018 that contained physiologically based pharmacokinetic (PBPK) models to understand how in vitro data are used in PBPK models to assess drug metabolism and predict DDIs. For evaluation of CLint and fm, 29 and 20 new drug applications were included for evaluation, respectively. For CLint, 86.2% of the PBPK models used modified values based on in vivo data with modifications ranging from –82.5% to 2752.5%. For fm, 45.0% of the models used modified values with modifications ranging from –28% to 178.6%. When values for CLint were used from in vitro testing without modification, the model resulted in up to a 14.3‐fold overprediction of the area under the concentration‐time curve of the substrate. When values for fm from in vitro testing were used directly, the model resulted in up to a 2.9‐fold underprediction of its DDI magnitude with an inducer, and up to a 1.7‐fold overprediction of its DDI magnitude with an inhibitor. Our analyses suggested that the in vitro system usually provides a reasonable estimation of fm when the drug metabolism by a given CYP pathway is more than 70% of the total clearance. In vitro experiments provide important information about basic PK properties of new drugs and can serve as a starting point for building a PBPK model. However, key PBPK parameters such as CLint and fm still need to be optimized based on in vivo data.